Building Sustainable Competitive Advantage Through Innovation in Sharia Financial Institutions: Bibliometric and Literature Review - Adi Sopian; Puspo Dewi Dirgantari; Lili Adi Wibowo; Ichsan Budiman; Siti Rohmat (Fakultas Ekonomi dan Bisnis Islam, 2025)
Innovation in Islamic Financial Institutions that are experiencing developments aims to make LKS competitive, sustainable and able to meet the needs of the community. For that, it is necessary to study innovation in Islamic financial institutions, because with innovation the company can survive. The research question is who are the authors who have contributed to the research, the development of research theme trends and future research trends regarding innovation in Islamic financial institutions. The novelty in this study is a research roadmap in the field of innovation in Islamic financial institutions. The method used in this study is bibliometric analysis by selecting data from reputable international sources and using the Scopus database, RStudio and Vosviewer tools. The findings in this study indicate that Muneeza, A. and Hassan, M.K. are the most influential authors in Islamic finance research dominated by issues of Islamic finance, banking, fintech, and zakat, with promising future research trends on the topics of digitalization of Islamic finance, productive waqf, and economic sustainability. The increasing number of research in the field of Islamic Financial Institution Innovation shows that this research theme is still very relevant in future research.